Numerical study of bioheat transfer in a vascular bed with counter-flow mechanisms - K.R. Sreegowrav; R. Indira; Sushma M. Puranik; S. Jagadeesha; S.J. Vishwanatha; K. Ganesh Kumar (Case Studies in Thermal Engineering)
Simulating and analyzing thermal behavior in the human body is crucial for various biomedical applications. The skin, composed of multiple layers, is connected to the vascular bed, which comprises venules and capillaries. Blood, the body's primary thermoregulator, flows towards the tissue through capillaries and away through venules. These blood vessels, separated by a thin layer of tissue, prevent mixing while enabling efficient heat exchange. Understanding this counterflow mechanism is vital for studying heat transfer within the vascular bed. In this study, the capillary, tissue, and venule are modeled as regions 1, 2, and 3, respectively, forming a three-layered rectangular channel. Heat transfer occurs via diffusion through the semi-permeable tissue layer, with slip conditions applied at its interface. The bioheat transport equation, combined with the Navier-Stokes equation, governs the thermal and fluid behavior. Analytical expressions for velocity are derived for all regions, while the temperature distribution, transformed into integral equations, is solved numerically. The resulting system of linear equations provides insights into the thermal dynamics within the vascular bed, with findings represented graphically.